Pengembangan Buku Penuntun Praktikum Sistem Ekskresi pada Manusia dengan Model Argument Driven Inquiry (ADI) - Yesi Yosinta; Neni Hasnunidah; Berti Yolida (Universitas Lampung, 2018)
Laboratory efficacy was supported by a practical guide book. This study aims to describe the validity and practicality of the manual excommunication manual of excretory systems in humans with an Argument Driven Inquiry (ADI) model that has been developed. This development research refers to the 4-D model proposed by Thiagaradjan covering define, design, develop, and disseminate stages. However disseminate was not done. The developed product was made with attractive cover, Baskerville Old Face letter with size 12, and EYD is good and correct. Expert and practitioner validation results showed 84% and 98% ideality scores with